Penentu Implementasi Skrining Hipotiroidisme Kongenital di Kalangan Ibu dengan Bayi Baru Lahir - Ani Kusniawaty; Ayu Laili Rahmiyati; Dyan Kunthi Nugrahaeni; Novie E. Mauliku; Budiman Budiman (Faletehan Health Journal, 2025)
The incidence of congenital hypothyroidism (CH) in Indonesia was estimated to be as high as 1 in 1,500 live births, significantly higher than in neighbouring countries such as Singapore, Malaysia, and Vietnam. However, despite efforts by the Ministry of Health to implement CH screening as part of maternal and child health services, the program's national coverage remains limited. This study aimed to identify factors influencing congenital hypothyroidism screening (CHS) implementation among mothers with newborns. The study was conducted at the Sekarwangi Health Center area, Sukabumi Regency, in 2023. This cross-sectional study used proportional random sampling to collect data from 291 respondents. Univariate, bivariate, and multivariate analyses were performed. Bivariate analysis showed that only the mother's occupation, time, and distance to healthcare facilities significantly influenced CHS implementation (p<0.05). Multivariate analysis revealed that the variables of occupation (p=0.016, PR=3.433), income (p=0.045, PR=2.348), marital status (p=0.023, PR=7.720), and accessibility of healthcare facilities (distance) (p<0.001, PR=2.055) were significant. Based on the analysis, accessibility to healthcare facilities (distance) was the most dominant factor influencing CHS implementation among newborns, followed by the variables of occupation, income, and marital status. Improving access to healthcare services is necessary, such as through the provision of mobile healthcare programs and digital-based education, to expand the coverage of screening.